Inovasi Pengelolaan Sampah Rumah Tangga Berbasis 3R (Reduce, Reuse, Recycle) di Desa Anjir Kabupaten Pulang Pisau - Helmi Helmi; Tati’ah Tati’ah; Roso Sugiyanto (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This community service activity is entitled Innovation in Household Waste Management Based on 3R (Reduce, Reuse, Recycle) in Anjir Village, Pulang Pisau Regency). This program is motivated by the increasing volume of household waste and the low practice of 3R-based management in Anjir Village, which has led to environmental and public health problems. The implementation method includes socialization, education, and training for residents on waste sorting, reducing the use of single-use plastics, reusing usable items, and processing organic waste with a household composter. In addition, this activity also introduced a digital waste bank system that facilitates the recording of deposits and waste savings results. The results of the activity show an increase in community understanding and skills in applying the 3R principle. The community has begun to get used to sorting waste, utilizing organic waste into compost, and saving inorganic waste through a waste bank. This program also encourages the growth of collective awareness about the importance of maintaining environmental cleanliness and opportunities for a circular economy based on waste. Overall, this community service activity produces a simple, applicable, and sustainable model for household waste management innovation. It is hoped that this model can be replicated in other villages as an effort to support waste reduction while improving environmental quality and community welfare.